UJI PERFORMA ALGORITMA NAIVE BAYES DALAM MENGKLASIFIKASI TIPE PERFEKSIONISME - Rizki Fauzi, (2023)
Perfectionism is the desire to achieve perfection accompanied by high standards based on the Multidimensional Perfectionism Scale (MPS) theory, which consists of three types: self-oriented perfectionism (SOP), other-oriented perfectionism (OOP), and socially-prescribed perfectionism (SPP). In this study, secondary data from previous research were used to test the performance of the Naive Bayes algorithm using k-cross validation in classifying the levels and tendencies of perfectionism types. The performance testing results in classifying the levels of each perfectionism type using undersampling were significantly better compared to the data without undersampling, with accuracy values ranging from 65% to 73%, precision ranging from 60% to 75%, recall ranging from 48% to 71%, and f-score ranging from 45% to 71%. Similarly, in classifying the tendencies of perfectionism types, the evaluation results with undersampling showed better performance, with an accuracy of 93%, precision of 94%, recall of 93%, and f-score of 93%.